Pollution in a Promised Land : An Environmental History of Israel - Tal, Alon, 1960- (Book collections on Project MUSE., 2002)
Virtually undeveloped one hundred years ago, Israel, the promised "land of milk and honey," is in ecological disarray. In this gripping book, Alon Tal provides--for the first time ever--a history of environmentalism in Israel, interviewing hundreds of experts and activists who have made it their mission to keep the country's remarkable development sustainable amid a century of political and cultural turmoil.